2012
DOI: 10.1038/aja.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and adverse effects of hormonal therapy for prostate cancer: Japanese experience and perspective

Abstract: Recently, novel anti-androgens and inhibitors of androgen biosynthesis have been developed through the elucidation of mechanisms of castration resistance of prostate cancer. We believe that these new developments will improve hormonal therapy. On the other hand, there has been an increase in criticism of hormonal therapy, because hormonal therapy is supposed to induce adverse effects such as cardiovascular disease. In this review, we have introduced the Japanese experience of hormonal therapy, because we belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
1
15
0
2
Order By: Relevance
“…One review study by Namiki et al . () reported that deaths from cardiovascular diseases in Japanese patients receiving hormonal therapy were not higher than those of the general population. They indicated that ethnic differences exist on the adverse effects of hormonal therapy in PC patients.…”
Section: Discussionmentioning
confidence: 95%
“…One review study by Namiki et al . () reported that deaths from cardiovascular diseases in Japanese patients receiving hormonal therapy were not higher than those of the general population. They indicated that ethnic differences exist on the adverse effects of hormonal therapy in PC patients.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with this, testosterone levels in prostate cancer tissues remain elevated after castration (approximately 25% of precastration levels) even though serum testosterone levels are lowered to <50 ng/dL by inhibiting gonadal androgen synthesis with ADT treatment (surgical or medical castration) . Therefore, treatment with agents that block testosterone production in the adrenal glands and tumor cells is warranted to mitigate tumor cell proliferation after surgical or medical castration using luteinizing hormone‐releasing hormone (LHRH) analogs …”
mentioning
confidence: 91%
“…Because ethnic diversities between Caucasians and Asians could influence the effectiveness of treatment, as well as the types of and susceptibility to adverse effects, studies validating clinical benefits of AA in CRPC patients of different ethnic backgrounds are encouraged. (10) Prior to the present study, with no clinical experience of this drug in Japanese patients, the recommended dose for AA in Japanese CRPC patients had not been established. The objective of the current phase-I study was to evaluate pharmacokinetics, pharmacodynamics, and preliminary efficacy and safety of AA in Japanese CRPC patients.…”
mentioning
confidence: 98%
See 2 more Smart Citations